MILD CHRONIC NaF INTAKE PROMOTES INSULIN RESISTANCE AND INCREASE IN INFLAMMATORY SIGNALING IN THE WHITE ADIPOSE TISSUE OF RATS - Chiba, Fernando Yamamoto [UNESP]; Saori Tsosura, Thais Veronica [UNESP]; Pereira, Renato Felipe [UNESP]; Lima Coutinho Mattera, Maria Sara de [UNESP]; Santos, Rodrigo Martins dos [UNESP]; Marani, Fernando [UNESP]; Saliba Garbin, Clea Adas [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Sumida, Doris Hissako [UNESP] (Int Soc Fluoride Research, 2019)
Excessive fluoride intake is associated with systemic metabolic alterations similar to those observed in type 2 diabetes such as decreased insulin secretion, impaired glycemic control, and insulin resistance. However, the underlying mechanisms for these changes are not fully understood. This study aimed to evaluate the effect of chronic NaF intake on insulin signaling and inflammatory pathways in the white adipose tissue (WAT) of rats. Seven-week-old castrated male Wistar rats were randomly distributed into 2 groups; a control group, which received 76.4 mg/L NaCl in their drinking water, and a fluoride group, which received 54.9 mg/L NaF in their drinking water and F present in their food pellets (total estimated fluoride intake = 4.0 mg/kg body weight/day). After 42 days, the WAT content of protein kinase B (PKB/Akt), c-Jun N-terminal kinase (JNK), inhibitor of kappa B kinase (I kappa K alpha/beta), and tumor necrosis factor alpha (TNF-alpha); as well as the phosphorylation status of Akt serine, Akt threonine, JNK, and I kappa K alpha/beta were evaluated by western blotting. The fluoride group showed a decrease in Akt serine phosphorylation status after insulin stimulation, and an increase in TNF-alpha content and I kappa K alpha/beta phosphorylation compared to the control group. No alteration was observed in the content of Akt, JNK, and I kappa K alpha/beta or in the phosphorylation status of JNK. Chronic NaF intake promoted attenuation of insulin signaling and activation of inflammatory signaling in the WAT of rats. These findings highlight the need for careful monitoring of fluoride intake to avoid its deleterious health effects.
Keywords: Diabetes mellitus; Inflammation; Insulin resistance